Pengaruh Latihan Mental Imagery dan Video Modelling Terhadap Keterampilan Shooting Bola Basket di Sekolah - Muhammad Yusuf Abdillah; Marisa Noviyanti Fajrah Ilsya; Tri Martini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect and compare the effectiveness of mental imagery and video modelling exercise methods on basketball shooting skills (free throw, three-point, and lay-up) among students at SMAN 1 Sumedang. This study applied a quantitative experimental method with a pre-test and post-test design. The sample consisted of 24 students evenly divided into three groups (n=8): Mental Imagery, Video Modelling, and Control. Since the data normality prerequisites were not met, hypothesis testing was conducted using non-parametric statistics. The Wilcoxon Signed Ranks Test results indicated that all groups experienced a significant score increase (p < 0.05) internally from pre-test to post-test. Furthermore, the Kruskal-Wallis H Test proved a highly significant difference in the effectiveness of the gain score simultaneously among the three groups (p = 0.000). Based on further analysis using the Mann-Whitney U Test, it was revealed that the video modelling method was the most effective intervention, recording the highest gain score improvement compared to the mental imagery method and the control group. The dominant mechanical improvement occurred in the lay-up and free throw components, while the three-point shooting was generally limited by the physical capacity of public school students. In conclusion, visual observation intervention through video modelling is highly recommended to accelerate students’ cognitive understanding and motor adaptation in basketball learning. Keywords: Non-Parametric Analysis, Motor Skills, Mental Imagery, Basketball Shooting, Video Modelling